Основные направления интеграции предприятий регионального туристского комплекса (Путеводитель предпринимателя)
In the conditions of dynamical growth of tourist streams complexity increase in service of weight of tourists and with insistence increase to convenience and quality of service timeliness, efficiency and clearness of accepted decisions becomes the main condition in maintenance of stability of tourist activity in region. This circumstance as practice has shown, causes aspiration to association various as the enterprises. The most widespread form is integration.